2020
DOI: 10.1155/2020/4871494
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Prevalence of Abortion and Risk Factors in Women: Evidence from a Cohort Study

Abstract: Background. 10-20% of pregnancies end due to spontaneous abortions. In recent years, nondocumentary evidence has been indicative of an increase in the prevalence of nonspontaneous abortions in Iran, especially in the Kurdish regions. The aim of this study is to assess the lifetime prevalence of spontaneous abortions and factors affecting spontaneous abortion in women 35-65 years old. Method. Data from the recruitment phase of Ravansar Non-Communicable Disease (RaNCD) cohort study was used. All of the 4831 marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
2
13
0
2
Order By: Relevance
“…Studies have shown that the incidence of spontaneous abortion is between 10 and 20% globally ( Cohain, Buxbaum, & Mankuta, 2017 ; Moradinazar et al, 2020 ). Majority of induced abortions, stillbirths and miscarriages occur in low-and middle-income countries (LMICs) and the sub-Saharan African region ( Bearak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the incidence of spontaneous abortion is between 10 and 20% globally ( Cohain, Buxbaum, & Mankuta, 2017 ; Moradinazar et al, 2020 ). Majority of induced abortions, stillbirths and miscarriages occur in low-and middle-income countries (LMICs) and the sub-Saharan African region ( Bearak et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…El principal resultado del presente estudio fue una ocurrencia del aborto espontáneo en 7,25 % de la población. Algunos estudios que han reportado este fenómeno muestran cifras similares (11)(12)(13). En China, en mujeres en edad fértil, se ha reportado que este fenómeno ocurrió en el 6,89 % de las mujeres embarazadas (11).…”
Section: Discussionunclassified
“…Otro resultado de interés fue el relacionado con la zona de procedencia, pues se encontró que el área urbana tenía mayor magnitud de aborto espontaneo (8,1 % vs 0,0 %), este resultado es similar al reportado por Moradinazar et al (13), en una muestra de mujeres iraníes.…”
Section: Discussionunclassified
“…There should not be any language barrier while doing the physical and hysteroscopy examination and a proper language translator should be provided. Early bleeding might be associated with miscarriage therefore it is recommended to evaluate thoroughly for the gynecological history of the patients [67][68][69] . Statistic's analysis suggests that out of four women one faces miscarriage issues.…”
Section: Early Pregnancy Issuesmentioning
confidence: 99%